Improving Cognitive Ability Through Educational Games in Early Childhood - Novita Loka; Raden Rachmy Diana (PROGRAM STUDI MAGISTER PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD) FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2022)
This research was carried out to provide knowledge or choices to parents and teachers or educators that cognitive development can be improved through playing educational games. This research is qualitative descriptive research. With data collection techniques of observation, interviews, and documentation. The subjects of the research were the children of class B Maria Al-Qibty Islamic Kindergarten Al-Ittifaqiah Indralaya Ogan Ilir South Sumatra, amounting to 20 people. The results showed that there was an increase in children's cognitive abilities through educational games. This is evidenced by the increased cognitive abilities of children with the application of educational games, such as being able to classify differences according to type and color, comparing shapes around them, understanding various number concepts, distinguishing large and small, long and short, time, space, and so on. able to make good pictures or designs.